Moments in time ultimate blast eruption at Karakatau - Mora, John; Billups, Scott ([United states] : Discovery Communications, 2005)
On May 20th, the volcano lets out a heavy rain of ash, and from there the eruption continues for weeks. Dutch volkano watchers take pictures more cones come to life with steam and smoke, and unusual phenomena such as solar haloes and blue moons are reported up to 187 miles away
Title from container
Executive producer, Stephen J. Eder ; editor, Shirin Bazleh ; sound, Grace Atkins
Hosted and narrated by James Woods
Keywords: Volcanoes; Krakatoa (Indonesia) -- Eruption, 1883